2003
DOI: 10.1002/uog.926
|View full text |Cite
|
Sign up to set email alerts
|

Fetal subcutaneous tissue thickness (SCTT) in healthy and gestational diabetic pregnancies

Abstract: Objective To determine reference values of fetal subcutaneous tissue thickness (SCTT) throughout gestation in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 27 publications
8
106
2
5
Order By: Relevance
“…Reduced subcutaneous fat mass has been shown in IUGR fetuses and the reduction is more significant when fat is normalized for body size. 41 On the other hand, in gestational diabetes mellitus the increased intrauterine growth is reflected in increased fetal fat mass deposition 42 and intrauterine ultrasound evaluation of fetal fat correlates with fetal leptin levels. 43 …”
Section: Evaluation Of Fetal Body Compositionmentioning
confidence: 99%
“…Reduced subcutaneous fat mass has been shown in IUGR fetuses and the reduction is more significant when fat is normalized for body size. 41 On the other hand, in gestational diabetes mellitus the increased intrauterine growth is reflected in increased fetal fat mass deposition 42 and intrauterine ultrasound evaluation of fetal fat correlates with fetal leptin levels. 43 …”
Section: Evaluation Of Fetal Body Compositionmentioning
confidence: 99%
“…However, this approach has not been confirmed by others and has not gained wide popularity. Others suggested that measuring subcutaneous fetal fat tissue (e.g., width/femur length ratio) achieves increased sensitivity and specificity (37)(38)(39)(40)(41). Moreover, assessment of sonographic markers for deviant fetal growth as the width of fetal fat layers, assessment of intraventricular septum width, and abdominal circumference were tested (42).…”
Section: Use Of Anthropometric Measurements For Assessment Of Fetal Gmentioning
confidence: 99%
“…Zbog svega toga, ultrazvučna procena adipoznog tkiva je korisna u evaluaciji abnormalnosti fetalnog rasta (Larciprete et al, 2003). Brojne studije izvele su ultrazvučna antropometrijska merenja fetalnog masnog tkiva.…”
Section: 9b Potkožno Masno Tkivo Fetusaunclassified
“…Brojne studije izvele su ultrazvučna antropometrijska merenja fetalnog masnog tkiva. Među najčešće evaluiranim je merenje masnog tkiva na nivou fetalnog abdomena, a što se izvodi lako i veoma brzo (Larciprete et al, 2003;Melamed et al, 2010). …”
Section: 9b Potkožno Masno Tkivo Fetusaunclassified
See 1 more Smart Citation